Cultural processes: A social psychological perspective - LEUNG, Angela K. Y. (Institutional Knowledge at Singapore Management University, 2010)
With the rapid growth of knowledge concerning ethnic and national group differences in human behaviors in the last two decades, researchers are increasingly curious as to why, how, and when such differences surface. The field is ready to leapfrog from a descriptive science of group differences to a science of cultural processes. The goal of this book is to lay the theoretical foundation for this exciting development by proposing an original process model of culture. This new perspective discusses and extends contemporary social psychological theories of social cognition and social motivation to explain why culture matters in human psychology. We view culture as a loose network of imperfectly shared knowledge representations for coordinating social transactions. As such, culture serves different adaptive functions important for individuals' goal pursuits. Furthermore, with the increasingly globalized and hyper-connected multicultural space, much can be revealed about how different cultural traditions come into contact. The authors discuss the psychological ramifications of these cultural interactions to illuminate the social and practical relevance of the proposed process model of culture.